E-commerce hosting solutions guide using WebSphere Commerce V5.5 business edition - McCollum, Chris (IBM redbooks., 2004)
This IBM Redbooks publication provides IT architects, IT specialists, and administrators with the critical knowledge to design, develop, implement, deploy, and manage a WebSphere Commerce V5.5 hosting site with multiple stores. This book includes: - An introduction to the WebSphere Commerce hosting model and the hosting composite pattern - An ITSO hosting example, including a business requirements analysis and solution design. - How to implement a team development environment, customize a store profile, and build, deploy, and manage multiple stores. - How to manage a hosting hub, hub organization, and hosted stores. - How to manage a hosted B2B store and organizations. - How to manage a hosted B2C store and organizations. The appendixes include procedures and tips for WebSphere Commerce implementation, WebSphere Commerce Studio implementation, common procedures, and error handling scenarios. Please note that the additional material referenced in the text is not available from IBM.